FAKTOR-FAKTOR PENYEBAB KEGAGALAN INVASI RUSIA ATAS UKRAINA - Riyanto, Sugeng (Universitas Jenderal Ahmad Yani, 2024)
Russia's invasion of Ukraine has been two years old. This large-scale military attack initially aimed to overthrow President Zelensky, who sought Ukraine to align with NATO. The anticipated swift campaign has so far failed to yield positive results for Russia, instead, the specter of failure looms large, with casualties on the Russian side, loss of territories held by Russia, and Russian defeats in battles in several regions. This paper aims to explore the reasons why the Russian invasion was unsuccessful. Using a perspective of war strategy and qualitative descriptive research methods, this study demonstrates that Russia's failure in the invasion of Ukraine is due to weak planning, weakness of logistics, morale of Russian troops, and rejection from the international community. Through an in-depth study of Russia's failure, this research contributes to the development of knowledge and enrichment of the understanding of the importance of geo-strategic factors in international relations.